Juridical Analysis of The Application of Local Currency Settlement Between Indonesia and China in Business Transactions - Putra, Tegar Islami (Faculty of Law, Universitas Negeri Semarang, 2023)
This article investigates the application of Local Currency Settlement (LCS) in transactions between Indonesian and Chinese businesses. The LCS framework is a settlement of bilateral trade transactions conducted by companies in Indonesia and partner countries using each country's currency. This research uses a normative legal research method that involves an in-depth review of the laws and regulations governing LCS and analyzing bilateral trade agreements between Indonesia and China. This method is used to interpret rules and regulations and bilateral trade agreements. In Indonesia, only banks that have met the criteria stipulated in Bank Indonesia Regulation No. 22/12/PBI/2020 can execute transactions using the LCS Framework. China also does the same to determine banks that can complete transactions using the LCS Framework. The advantages of the LCS Framework in the perspective of trade between countries can be seen in terms of mechanism, community productivity, and data security. Meanwhile, the LCS Framework's shortcomings can be seen from the perspective of the stability of each country, which can affect transactions.